1983
DOI: 10.2170/jjphysiol.33.69
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular calcium store and transport of elements in acinar cells of the salivary gland determined by electron probe X-ray microanalysis.

Abstract: Electron probe X-ray microanalysis using freshly frozen hydrated and dried thin sections of dog submandibular gland was performed to determine the distribution of elements and water in the acinar cells of resting and stimulating states. The results obtained are as follows : (a) The secretory granules contained high concentrations of Ca and S while high concentrations of K and P were present in the cytoplasm and/or nucleus of acinar mucous cells of the gland in the resting state. (b) With pilocarpine stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
23
1

Year Published

1983
1983
1997
1997

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 28 publications
8
23
1
Order By: Relevance
“…None the less, the submandibular gland acinar cytoplasmic results of Sasaki et al (1983) 300 mmol/kg dry mass and K to decrease to about 400 mmol/kg dry mass following pilocarpine stimulation (Table 2). Similar Na and K changes but of smaller magnitude were observed in dog pancreatic acini (Table 2).…”
Section: Comparisons With Previous X-ray Microanalysis Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…None the less, the submandibular gland acinar cytoplasmic results of Sasaki et al (1983) 300 mmol/kg dry mass and K to decrease to about 400 mmol/kg dry mass following pilocarpine stimulation (Table 2). Similar Na and K changes but of smaller magnitude were observed in dog pancreatic acini (Table 2).…”
Section: Comparisons With Previous X-ray Microanalysis Resultsmentioning
confidence: 99%
“…Somlyo, Somlyo & Shuman (1979) confirmed the validity of Hall's method for ultra-thin cryosections in the freeze-dried state. Gupta & Hall (1983) used the technique to study cockroach salivary glands; Sasaki, Nakagaki, Mori & Imai (1983) K. T. IZUTSU AND D. E. JOHNSON and Roomans, Wei, Ceder & Kollberg (1982) to study mammalian submandibular salivary glands; and Muller & Roomans (1984) to study the resting rat parotid gland.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous data obtained by X-Ray microanalysis in canine submandibular gland revealed that cellular organelles such as granules had a higher Cl-concentration than in cytoplasm (SASAKI et a!., 1983). When perfused with the low Na+ solution (41.15 mM concentration : n=10, 2 glands), the a,1, 4?Pm, and E01 were 62.5±1.2 mM (S.E.…”
Section: N=41 5 Glands)mentioning
confidence: 87%
“…Secretory granules. Thin section studies (Izutsu and Johnson, 1986;Izutsu et al, 1985;Sasaki et al, 1983) indicate that secretory granules typically have higher concentrations of Ca, and lower concentrations of K and P when compared with the cytoplasmic and nuclear concentrations of these elements (Table 3, Fig. 1).…”
Section: Electron Probe X-ray Microanalysismentioning
confidence: 99%